2007
DOI: 10.1590/s1517-86922007000500006
|View full text |Cite
|
Sign up to set email alerts
|

Atividade eletromiográfica no agachamento nas posições de 40º, 60º e 90º de flexão do joelho

Abstract: O objetivo deste estudo foi comparar a atividade eletromiográfica (EMG) dos músculos reto femoral, bíceps femoral, tibial anterior e sóleo no agachamento, associando a posição de tronco ereto com 2 ângulos de flexão do joelho (40° e 60°) e a posição de tronco fletido a 45° com 3 ângulos de flexão do joelho (40°, 60° e 90°). Todas as combinações foram realizadas com e sem acréscimo de carga (10kg). A amostra foi composta por 12 indivíduos saudáveis com idade de 21,1 ± 2,5 anos e massa corporal de 62,8 ± 7,4kg. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
0
7
0
9
Order By: Relevance
“…They found 112 injuries among all the study participants, and concluded that most injuries occurred during maneuvers, in contact with the board and with the seabed, suggesting that the extrinsic factors inherent to this sport are potentially harmful to athletes. Sousa et al 15 compared the electromyographic activity (EMG) of the rectus femoris, biceps femoris, tibialis anterior and soleus muscles in squatting, associating the trunk in upright position with two angles of knee flexion (40° and 60°) and the trunk at 45° flexion with three angles of knee flexion (40°, 60° and 90°). Trunk position and the additional load of 10 kg influenced the muscular activation of the femoris rectus at 60° of knee flexion, in which the erect trunk provided more activation.…”
Section: Discussionmentioning
confidence: 99%
“…They found 112 injuries among all the study participants, and concluded that most injuries occurred during maneuvers, in contact with the board and with the seabed, suggesting that the extrinsic factors inherent to this sport are potentially harmful to athletes. Sousa et al 15 compared the electromyographic activity (EMG) of the rectus femoris, biceps femoris, tibialis anterior and soleus muscles in squatting, associating the trunk in upright position with two angles of knee flexion (40° and 60°) and the trunk at 45° flexion with three angles of knee flexion (40°, 60° and 90°). Trunk position and the additional load of 10 kg influenced the muscular activation of the femoris rectus at 60° of knee flexion, in which the erect trunk provided more activation.…”
Section: Discussionmentioning
confidence: 99%
“…O exercício de agachamento é muito utilizado nos últimos anos tanto em treinamento de atletas como em programas de reabilitação [1]. Ao analisar a biomecânica do movimento identifica-se que essa atividade com suporte de peso além de estimular os músculos o glúteo, grácil e os outros músculos da coxa e do abdome, gera aumento da pressão intra-abdominal e, consequentemente, ocasiona uma força oposta aos movimentos dos músculos do assoalho pélvico (MAP).…”
Section: Introductionunclassified
“…These symptoms are due to structural or biomechanical changes of the joint, which is exacerbated by activities of small, medium and great efforts. Other signs are also present such as patellar cracking, edema, and articular block 2 . Its etiology has not yet been clearly established, and may be related to biomechanical alterations, specifically, the static and dynamic imbalance.…”
Section: Introductionmentioning
confidence: 99%